PAPR Reduction Performance by Active Constellation Extension for Diversity MIMO-OFDM Systems - Theodoros Tsiligkaridis; Douglas L. Jones (Journal of Electrical and Computer Engineering)
The V-BLAST wireless communication architecture, space-time block code (STBC), and space-frequency block code (SFBC) techniques are strong candidates for achieving very high data rates in 4G broadband wireless communications. This paper extends the efficient Active Constellation Extension Smart Gradient-Project (ACE-SGP) peak-to-average power (PAPR) reduction method to STBC, SFBC, and V-BLAST systems. Simulation results show 4.19 and 3.57 dB of PAPR reduction for the Alamouti STBC and SFBC, respectively.